Chat GPT and Human Resource Management - Silva, Marlene; Costa , Daniela (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Artificial intelligence is increasingly being used and we have all become accustomed to references to chatbots, virtual assistants, and machine learning, among others. This evolution is taking place in various areas such as health, finance, marketing, and certainly in the field of human resource management. The goal is to help automate routine tasks, improve the efficiency and effectiveness of processes, and provide valuable outputs for strategic decision-making. The advent of ChatGPT has further strengthened support for the Human Resources area, having a very wide-ranging application, but which can also be personalized according to the real needs of the organization. But what is ChatGPT? It is a language model created by Open AI and based on GPT - Generative Pretrained Transformer, (an unsupervised language neural network that was trained using massive amounts of internet data). It is specifically designed to understand the context and intention of a question or conversation, and respond appropriately. The purpose of the training is to allow the model to generate text based on input provided, producing answers to questions or continuing a conversation in a natural way. The potential of ChatGPT is vast, with many companies keeping a close eye on its technology and how its use can improve their solutions. At the level of Human Resource Management, we can immediately indicate some examples of ChatGPT application: i) automate repetitive tasks (ChatGPT can be programmed to perform repetitive tasks such as resume classification and analysis, virtual interviews, and performance report generation); ii) provide accurate and updated information (it can be trained to answer frequent questions about benefits, company policies, etc.); iii) increase efficiency (it can increase the efficiency of the recruitment, performance feedback, and training processes, allowing companies to achieve better results in less time); iv) generate documents (such as employment and services contracts, termination letters performance reports,, internal communication documents); v) perform natural language processing tasks, such as automatic translation, text summarization, and text generation. Eurotux Group is not indifferent to this type of technological advances. We constantly seek the continuous improvement of our processes and good practices, through efficient and flexible organization models.We also seek to follow a proactive approach of foresight and technological innovation, with a view to developing and implementing innovative solutions, capable of adding value to the market. As such, a common challenge was launched across all areas of the company, to discover how the use of ChatGPT could create more internal benefits, thereby improving its position in the market. In Human Resource Management area this technology is already being used in different aspects. In this presentation, we will present wich processes we are working with this tool and we will also show that it was possible to ChatGPT improve Human Resources processes, not as a substitute solution for human decision-making, but as a supportive tool. The Human Resources Professional must use the tool correctly, being responsible for evaluating the results generated and taking the necessary decisions, based on existing ethical and organizational cultural considerations.